Moderate Exercise Training Attenuates the Severity of Experimental Rodent Colitis: The Importance of Crosstalk between Adipose Tissue and Skeletal Muscles - Jan Bilski; Agnieszka I. Mazur-Bialy; Bartosz Brzozowski; Marcin Magierowski; Katarzyna Jasnos; Gracjana Krzysiek-Maczka; Katarzyna Urbanczyk; Agata Ptak-Belowska; Malgorzata Zwolinska-Wcislo; Tomasz Mach; Tomasz Brzozowski (Hindawi Limited, 2015)
Although progress has been recently made in understanding of inflammatory bowel diseases (IBD), their etiology is unknown apart from several factors from adipose tissue and skeletal muscles such as cytokines, adipokines, and myokines were implicated in the pathogenesis of ulcerative colitis. We studied the effect high-fat diet (HFD; cholesterol up to 70%), low-fat diet (LFD; cholesterol up to 10%), and the normal diet (total fat up to 5%) in rats with TNBS colitis forced to treadmill running exercise (5 days/week) for 6 weeks. In nonexercising HFD rats, the area of colonic damage, colonic tissue weight, the plasma IL-1β, TNF-α, TWEAK, and leptin levels, and the expression of IL-1β-, TNF-α-, and Hif1α mRNAs were significantly increased and a significant fall in plasma adiponectin and irisin levels was observed as compared to LFD rats. In HFD animals, the exercise significantly accelerated the healing of colitis, raised the plasma levels of IL-6 and irisin, downregulated the expression of IL-1β, TNF-α, and Hif1α, and significantly decreased the plasma IL-1β, TNF α, TWEAK, and leptin levels. We conclude that HFD delays the healing of colitis in trained rats via decrease in CBF and plasma IL-1β, TNF-α, TWEAK, and leptin levels and the release of protective irisin.